Estudo dos efeitos comportamentais e neuroquímicos do extrato padronizado de Justicia pectoralis (chambá) em camundongos - Venâncio, Edith Teles (2009)
The standardized extract of chamba, prepared from the aerial parts of Justicia pectoralis Jacq. var stenophylla Leonard, was evaluated in classical animal models to the screening of drugs with activity in axiety, depression, sedation and convulsion, such as elevated plus maze (EPM), light/dark, open field, rota rod, forced swimming, tail suspension, pentobarbital-induced sleep time and pentilenotetrazole-induced seizures and a neurochemistry study, through the level of monoamines and its metabolites, such as dopamine (DA), 3,4-dihydroxyphenyl acetic acid (DOPAC), homovanilic acid (HVA), norepinephrine (NE), 5-hydroxytryptamine (5HT) and 5-hydroxyindoleacetic acis (5HIAA). Chambá was administered acutely in all tests, in the doses of 50, 100 and 200 mg/kg, through the oral via (p.o.). Results showed that the extract presented an anxiolytic effect in the models of EPM and light/dark, since increased all the parameters analyzed in the EPM, such as NEOA, PEOA, TPOA, PTOA, as well as the permanence time in the light compartment. This effect is probably related with the GABAergic system since Flumazenil, an antagonist of GABAA/benzodiazepinic, reversed the anxiolytic effect of chamba in the EPM. In the open field, it was not observed any alteration in the locomotor activity, as well as the number of grooming and rearing. Chamba presented depressor effect of Central Nervous System (CNS), since in the forced swimming and tail suspension, increased the immobility time of animals. The sedative/hypnotic evaluation of chamba, in pentobarbital-induced sleep time showed that it has no alteration in the duration of sleep of animals, discarding sedative effect. In the pentilenotetrazole-induced seizures, chamba did not change the convulsion latency, as well the death latency. This result suggests that chamba did not have anticonvulsivant effect. The neurochemistry evaluation comproved the depressor effect of the extract, since it was verified a reduction in the level of monoamine levels, involved in the depression. In conclusion, these effects showed that chamba presented anxiolytic effect, probably related with the GABAergic system and depressor effect disproved anticonvulsant and sedative effects.